2020
DOI: 10.1177/1099800419899730
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Pathways Associated With Term Labor Induction Course in African American Women

Abstract: Objectives: The purpose of this study was to evaluate differences in the metabolic pathways activated in late-pregnancy serum samples among African American women who went on to have term (≥37 weeks) labor induction requiring high total oxytocin doses to complete first-stage labor compared to those in similar women with low-oxytocin labor inductions. Study Design: Case–control study ( N = 27 women with labor induction with successful cervical ripening: 13 requiring the highest total doses of synthetic oxytocin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Most of the human metabolite profiling in parturition focused on maternal serum and amniotic fluid. Partly consistent with previous studies on mouse uterine muscle and human serum during labor [17, 18], we found that the greatest changes were observed in lipolysis and fatty acid oxidation between nonlabor and labor stages. Compared with patients from the nonlabor group, those from the labor group had increased myometrial levels of several fatty acids generated as byproducts of β-oxidation and decreased triacylglycerol level, presumably owing to increased lipolysis.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the human metabolite profiling in parturition focused on maternal serum and amniotic fluid. Partly consistent with previous studies on mouse uterine muscle and human serum during labor [17, 18], we found that the greatest changes were observed in lipolysis and fatty acid oxidation between nonlabor and labor stages. Compared with patients from the nonlabor group, those from the labor group had increased myometrial levels of several fatty acids generated as byproducts of β-oxidation and decreased triacylglycerol level, presumably owing to increased lipolysis.…”
Section: Discussionsupporting
confidence: 92%
“…The Benjamini-Hochberg FDR method (Hochberg & Benjamini, 1990) was used for multiplehypothesis correction to identify individual metabolites based on a q value of .20. As reported in previous literature (Carlson et al, 2020), the FDR correction protects against type I error but it may exclude true positive metabolites (type II error). Thus, metabolic pathways associated with PNS and the PNS cluster were determined with a raw p value of .05 (Chandler et al, 2016).…”
Section: Discussionmentioning
confidence: 80%
“…Oxytocin administration is the primary pharmacological intervention used during the course of labor 65 , 66 and is frequently used for labor induction 67 , rates of which have risen from 9.5% of births in 1990 68 to 31.4% of births in 2020 69 . Intrapartum dose requirements for oxytocin have been found to vary by body mass index (BMI) 70 , 71 and maternal age 72 , and may be influenced by differences in lipid metabolism 73 . While use of oxytocin for labor stimulation may be a life-saving intervention, overuse can expose the mother to risks, including postpartum hemorrhage 74 – 76 .…”
Section: Introductionmentioning
confidence: 99%